Si‐based Ge0.9Sn0.1 photodetector with peak responsivity of 2.85 A/W and longwave cutoff at 2.4 μm. Issue 11 (1st May 2015) - Pham, T.N.; Du, W.; Conley, B.R.; Margetis, J.; Sun, G.; Soref, R.A.; Tolle, J.; Li, B.; Yu, S.‐Q.
Abstract : High performance Si‐based Ge0.9 Sn0.1 photoconductive infrared detectors have been demonstrated. The device fabrication is fully compatible with the complementary metal‐oxide‐semiconductor (CMOS) process. The room temperature responsivity at 1.55 μm is 0.26 A/W and comparable with that of commercially available InGaAs and Ge photovoltaic detectors. Temperature‐dependent study shows an increased peak responsivity of 2.85 A/W at 77 K. The spectral response has a longwave cutoff of 2.4 and 2.2 μm at 300 and 77 K, respectively. Specific detectivity (D*) was calculated and compared side by side with D* of market dominating infrared detectors.